Prithvi Mata: Hindu Perspectives on Nature - Joseph Archer (Dr. Chinmay Pandya, 2020)
Indian scriptures describe the unity of each individual with nature by stating I am the Son of Mother Earth (mother earth). I found two major takeaways from my interviews in India. Firstly, I was fascinated to see so much agreement on the concept of species dharma. This concept is, in my opinion, the strongest evidence of embedded Hindu ecological understanding. The concept is very applicable and accessible to average Hindus, making it a framework that, if promoted, can help modern India develop a stronger environmental ethic. Through my own observations I have commonly witnessed what I can only define as spiritual apathy. Walking across a bridge I watched a family dump bags of candy, wrapper and all, into the river. Hundreds of aluminum and plastic bowls from makeshift Ganga puja litter the shore of the river, with untold thousands lying at the bottom. The main cause behind the so-called 'ignorant practice' in Hinduism seems to be the failure of the priests. Indeed, there is a need of class of Brahmin who has attained a state of higher consciousness and can teach masses with their ancient wisdom. Literacy on the legacy of ancient wisdom is on the rise in India, allowing the less-educated to access religious texts in a way that they never have been able to. A woman, who was interviewed said, "if we take our own inner change seriously, than this will lead to outer change. If we change our vision and lifestyle, everything will shift. We must perceive nature, culture, and land as divine".